INNOVATIVNESS IN BOSNIAN SMALL AND MEDIUM SIZED ENTERPRISES - Zijad Džafić; Admir Omerbasic (Economic Review)
Small and medium-sized enterprises (SMEs) are one of the key development factors of the economy in many countries. They stimulate competitiveness and innovativeness, contribute to the growth of employment and also have an impact on improving the overall economic situation in the country. Bosnia and Herzegovina is a transition country that has still not adequately organized the development concept of small and medium-sized enterprises. In Bosnia and Herzegovina (BiH) there is an entrepreneurial initiative but without significant government support in the realization of business ideas of potential entrepreneurs or the implementation of innovative ideas, although their personal success generates and benefits the whole society. The central research hypothesis reads: Innovation has a positive impact on the growth and development of small and medium-sized manufacturing enterprises in BiH. The authors seek to present the current state of innovativeness in the SME sector in BiH with a review of the situation in the countries of the region and to propose certain measures to accelerate their development. This paper uses the Global Innovation Index Reports, followed by the World Bank Report on Business Ease, which measures the degree of national competitiveness and innovation of the economy, as well as the results of primary research on a sample of 200 manufacturing SMEs in BiH. The general objective of the research in this paper is to consider and review the effects of innovations in the operations of emerging SMEs and their impact on the growth of market share and increase of the total revenue.